2022
DOI: 10.1111/pan.14386
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to operating room readiness for airborne precautions using simulation‐based clinical systems testing

Abstract: Background The emergence of the COVID‐19 disease as a global pandemic caused major challenges and strained busy operating room environments. This required institutions to rethink current system functioning and urgently develop safe medical practices and protocols. Purpose To use a novel approach combining simulation‐based clinical system testing with rapid cycle deliberate practice concepts for identifying latent safety threats presented by newly developed operating room COVID‐19 protocols and collecting front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…In contrast to our operating room COVID-19 simulation-based clinical systems test, in which we trained only 2 anesthesia staff members at a time with a single scenario, the ED is a much more complex system requiring testing with 5 scenarios, a larger number of providers at a time, and more detailed observation. 40 In both cases, our novel method combined rapid-cycle simulation training with a simulation-based clinical systems testing approach to define latent safety threats and develop responses. During this outbreak, the onsite simulation process was modified to take on a systems-based testing perspective.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to our operating room COVID-19 simulation-based clinical systems test, in which we trained only 2 anesthesia staff members at a time with a single scenario, the ED is a much more complex system requiring testing with 5 scenarios, a larger number of providers at a time, and more detailed observation. 40 In both cases, our novel method combined rapid-cycle simulation training with a simulation-based clinical systems testing approach to define latent safety threats and develop responses. During this outbreak, the onsite simulation process was modified to take on a systems-based testing perspective.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the methods from our recent work in the operating room and developed 5 rapid onsite cycle ED simulation cases related to new protocols coupled with a structured observation tool. 40 The research team observed simulations logged adherence to protocols, identified latent safety threats, and participating staff were encouraged to provide input regarding potential solutions, and the case block was repeated with the suggested strategies. After each exercise, participants completed a web-based evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations